Differences in body composite and physical match performance in female soccer players according to team position - Milanovic, Z.; Sporis, G.; Trajkovic, N. (Journal of Human Sport & Exercise, 2012)
The aim of this research was to determine the differences between body composition and physical match performance among female soccer players according to the team`s position. Twenty two elite female soccer players (aged 23.95 ± 4.52, height 168.82 ± 7.19 cm, body mass index 21.5 ± 1.3 kg) from Serbian A-national team participated in this study. Players were tested for aerobic endurance, Yo-Yo intermittent recovery test level 1 (YYIRL1), body mass and body height. The Percentage of Body Fat and Body mass index (BMI) was determine according to body height and body weight parameters. The average value of body weight among female soccer players has been 61.4±6.0kg. The biggest average value for Body weight has been found among midfielders 62.7±7.7kg, while the smallest values have been found among goalkeepers 59.5±10.6kg. Opposite to the body weight, goalkeepers have been the tallest players with average body high of 172.5±3.5cm, than the defenders with 170.0±7.2cm, while the midfielders (168.7±8.7cm) and the attackers (164.7±5.0cm) have shown the smallest average values. The YYIRL1 test`s results have shown that all positions have similar value within range of 880-930m, which indicates group homogeneity. The average values of the body fat was 25.9±2.0%. Significant difference between the tested variables according to the player`s position in the team could not be established (p<0.05). The selection process and the orientation towards specific team position represent an important aspect of the realization of the top athletic results, but it cannot be based merely on morphological and functional results. According to this research, differences cannot be precisely defined in both morphological and functional abilities of the women soccer players based on their position in the team.